2019
DOI: 10.1039/c9sm00686a
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in colloidal gel strands

Abstract: A colloidal gel strand deforming plastically prior to breakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Particle-resolved studies of dynamic heterogeneity in gels began with Gao and Kilfoil who found distinct populations of slow and fast particles [83]. Later work confirmed this [85,86,191,192] as shown in Fig. 12(a).…”
Section: Short-time Dynamicsmentioning
confidence: 80%
“…Particle-resolved studies of dynamic heterogeneity in gels began with Gao and Kilfoil who found distinct populations of slow and fast particles [83]. Later work confirmed this [85,86,191,192] as shown in Fig. 12(a).…”
Section: Short-time Dynamicsmentioning
confidence: 80%
“…Above all, it shows that the ratio T /µ can be used to significantly change the failure response of a network. In relating this knowledge to soft matter systems, a clear challenge is to better understand the influence of the physics at the element level, such as plastic rearrangements in colloidal gel strands [37] and temperature sensitivity of elastic elements such as semi-flexible fibres [38].…”
Section: Discussionmentioning
confidence: 99%
“…8 Therefore, quantitative descriptions of the microstructure and dynamics of such materials are crucial to reveal the mechanisms accounting for the desired mechanical properties. Most experimental, 9 11 simulation, 12 15 and theoretical studies have focused on systems with attractive interactions between particles because of depletion attraction induced by a nonadsorbing polymer or depletion-like Morse potential. Attraction mediates the formation of sample-spanning clusters, which dynamically arrest to create a gel which is heterogeneous in local connectivity, mesoscopic structure, and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quantitative descriptions of the microstructure and dynamics of such materials are crucial to reveal the mechanisms accounting for the desired mechanical properties. Most experimental, simulation, and theoretical studies have focused on systems with attractive interactions between particles because of depletion attraction induced by a nonadsorbing polymer or depletion-like Morse potential. Attraction mediates the formation of sample-spanning clusters, which dynamically arrest to create a gel which is heterogeneous in local connectivity, mesoscopic structure, and dynamics. Such colloidal gels derive their rigidity from physically bonded particles which form strands and connecting nodes that develop into a percolating elastic network. , Restructuring these networks due to external or internal stresses is governed by events happening at the individual particle level, as the bonds between the particles are typically weak; a relation between local connectivity and thermally activated dynamics at the individual particle level has been reported recently for a depletion-induced colloidal gel. , …”
Section: Introductionmentioning
confidence: 99%